Implementasi Sistem Informasi Verifikasi Klaim BPJS Pasien IGD Menggunakan Metode Agile - Istiqomah, Nurul; Abdussalaam, Falaah; Yunengsih, Yuyun (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Rapidly developing technology can support various human activities or performance, one of which is the performance of hospital employees who work on emergency patient medical record installations which are not yet fully optimized and computerized. Various problems were found, such as recording BPJS claims reports which were still manual and only relied on programs such as Microsoft Excel, errors in making Patient Eligibility Letters (SEP) which resulted in data being delayed so that the BPJS claims process was hampered or claims were pending. Therefore, an information system is needed that is useful for making the performance of medical records employees more effective in making BPJS claim verification reports for emergency room patients more easily, quickly and accurately. The development method used by researchers in this research is the Agile method, while the research data collection method includes observation, interviews, documentation with descriptive analysis. From the results of the design, an information system design was produced with various methods chosen to streamline the performance of medical records employees in preparing BPJS claim verification reports for emergency room patients, thereby producing accurate and complete data. Able to optimize services and reduce data errors that result in delayed claims, maintain the confidentiality of claims data and also control the completeness of files and improve the quality of service at the hospital.